ChemInform Abstract: Low Temperature Synthesis of Silicon Carbide Nanomaterials Using a Solid‐State Method. Issue 40 (12th September 2013) - Dasog, Mita; Smith, Larissa F.; Purkait, Tapas K.; Veino, Jonathan G. C.
Abstract Controlled morphologies of β‐SiC nanocrystalline materials are prepared via solid‐state metathesis reaction of sol‐gel derived SiO2 nanospheres, nanorods, and nanofibers, together with Mg and C powders (600 °C).